Transesophageal echocardiography in orthotopic liver transplantation: a comprehensive intraoperative monitoring tool - Luigi Vetrugno; Federico Barbariol; Umberto Baccarani; Francesco Forfori; Giovanni Volpicelli; Giorgio Della Rocca (Critical Ultrasound Journal, 2017)
Abstract Intraoperative transesophageal echocardiography is a minimally invasive monitoring tool that can provide real-time visual information on ventricular function and hemodynamic volume status in patients undergoing liver transplantation. The American Association for the Study of Liver Diseases states that transesophageal echocardiography should be used in all liver transplant candidates in order to assess chamber sizes, hypertrophy, systolic and diastolic function, valvular function, and left ventricle outflow tract obstruction. However, intraoperative transesophageal echocardiography can be used to “visualize” other organs too; thanks to its proximity and access to multiple acoustic windows: liver, lung, spleen, and kidney. Although only limited scientific evidence exists promoting this comprehensive use, we describe the feasibility of TEE in the setting of liver transplantation: it is a highly valuable tool, not only as a cardiovascular monitoring, but also as a tool to evaluate lungs and pleural spaces, to assess hepatic vein blood flow and inferior vena cava anastomosis and patency, i.e., in cases of modified surgical techniques. The aim of this case series is to add our own experience of TEE as a comprehensive intraoperative monitoring tool in the field of orthotopic liver transplantation (and major liver resection) to the literature.